The attitude of employees in perioperative nursing to training new employees in the workplace - Oblak, Tina (Obzornik zdravstvene nege, 2017)
Introduction: There has been little research on systematic training of new employees in perioperative nursing. The aim of the present study was to establish whether the attitude of the employees in perioperative nursing towards the training of new employees in the workplace is connected to their education in perioperative nursing, workload, work competence or attitude of new employees in perioperative nursing. Methods: A quantitative exploratory research was performed in March 2017 and data was collected by means of a structured survey questionnaire. Perioperative nursing staff working in a selected Slovenian hospital's operating theatres, who are trained well enough to work independently (n = 69) and have at least one year of working experience, were questioned to obtain a purposive sample. Descriptive statistics, the Pearson correlation coefficient and factor analysis are shown. Results: Employees in perioperative nursing gladly transmit their knowledge and experience (x = 4.79), growing professionally as they do so ( = 4.63). They see the training of new employees as their personal challenge (x = 4.17). The knowledge of the respondents was shown to be a factor that is marginally positively associated (r = 0.278, p = 0.021) with the attitude to training new employees in the workplace. The training that experienced employees in perioperative nursing have received, their competencies, workload, and their opinion of the work of the new employees, are not connected to the attitudes they posses when training these new employees in the workplace. Discussion and conclusion: The study indicates the need to establish definined criteria relating to the employment of candidates, and may contribute toward the future design of a systematic training course in perioperative nursing.
Keywords: competency assessment; development of professional competencies; knowledge transfer; ocena usposobljenosti; prenos znanja; profesionalni odnos; professional attitude; razvoj poklicnih kompetenc; situacijsko učenje; situational learning; učenje na delovnem mestu; workplace learning